IMPLEMENTATION OF INTEGRATIVE THEMATIC LEARNING IN THE 2013 CURRICULUM THE INDEPENDENT CURRICULUM WAS INTEGRATED AT SDN 61 JEULINGKE BANDA ACEH - Mariana Hardianti; Moh. Yudi Nursyaid; Abdul Hakim; Siti Mayang Sari; Lili Kasmini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research aims to describe the implementation of integrativethematic learning in the 2013 independent curriculum at SDN 6 JeulingkeBanda Aceh. The method in this research is descriptive qualitative whichdescribes the real conditions at the time of the research. The subjects of thisresearch were the principal, class I and IV teachers, as well as administrativestaff. Data collection techniques include interviews and documentation withseveral of these subjects. Researchers want to know the curriculumimplemented at SDN 61 Jeulingke Banda Aceh with integrative thematiclearning, what obstacles were found during implementation, as well as the roleof the school in making the independent curriculum a success. The researchresults show that the implementation of integrative thematic learning in the2013 curriculum has gone well in accordance with government policy. The newindependent curriculum has been implemented at SDN 61 Jeulingke BandaAceh for the last 3 months in grades I and IV. While implementing integrativethematic learning in the 2013 curriculum so far there have been no problemsbecause the teachers refer to guidelines in the form of books and syllabi.However, in this independent curriculum, SDN 61 Jeulingke Banda Aceh doesnot use integrative thematics because the learning is separated according to thetextbook the teacher receives, unlike the 2013 curriculum which combinesseveral materials into one theme.